2013
DOI: 10.1111/brv.12056
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of the hearts of lizards and snakes

Abstract: With approximately 7000 species, snakes and lizards, collectively known as squamates, are by far the most species-rich group of reptiles. It was from reptile-like ancestors that mammals and birds evolved and squamates can be viewed as phylogenetically positioned between them and fishes. Hence, their hearts have been studied for more than a century yielding insights into the group itself and into the independent evolution of the fully divided four-chambered hearts of mammals and birds. Structurally the heart is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
185
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(192 citation statements)
references
References 247 publications
(368 reference statements)
7
185
0
Order By: Relevance
“…By contrast, mammals, birds and crocodilians have two anatomically distinct atria and ventricles, wherein the right atrium exclusively fills the right ventricle with oxygen-poor systemic venous blood, and the left atrium supplies the left ventricle with oxygenated blood returning from the lungs. Anatomically 'intermediate' are the hearts of amphibians and non-crocodilian reptiles (turtles, lizards and snakes), where oxygen-poor and oxygen-rich blood from the right and left atria converge within a single ventricle (Hicks, 2002;Jensen et al, 2014). Reptiles thus present an ideal paradigm to investigate the evolution of ventricular complexity coupled to the double circulatory system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, mammals, birds and crocodilians have two anatomically distinct atria and ventricles, wherein the right atrium exclusively fills the right ventricle with oxygen-poor systemic venous blood, and the left atrium supplies the left ventricle with oxygenated blood returning from the lungs. Anatomically 'intermediate' are the hearts of amphibians and non-crocodilian reptiles (turtles, lizards and snakes), where oxygen-poor and oxygen-rich blood from the right and left atria converge within a single ventricle (Hicks, 2002;Jensen et al, 2014). Reptiles thus present an ideal paradigm to investigate the evolution of ventricular complexity coupled to the double circulatory system.…”
Section: Introductionmentioning
confidence: 99%
“…Blood returning from the lungs arrives at the cavum arteriosum from where it is pumped into the left (LAo) and right (RAo) aortic arches via the cavum venosum (Hicks, 2002). The cavum arteriosum and cavum venosum are partially separated from the cavum pulmonale by a myocardial structure known as the muscular ridge (MR) (van Mierop and Kutsche, 1985;Hicks, 2002;Jensen et al, 2014). The MR can effectively separate pulmonary and systemic venous blood within the ventricle, as illustrated by numerous classical studies demonstrating that blood emanating from the systemic arches and pulmonary artery differ substantially in their oxygen concentrations in turtles (Steggerda and Essex, 1957), snakes (White, 1959) and lizards (Foxon et al, 1956;White, 1959).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We prefer to address this structure as 'folding septum'. The presence and extent of the vertical septum (homologous to inlet septum) differs among reptiles, being virtually absent in turtles and most non-crocodilian reptiles, but more prominent in varanids and pythonidae [11]. In the python myocardial apical trabeculations traverse the ventricle to partly separate the cavum pulmonale from the cavum arteriosum.…”
Section: Septum Components In Reptilian Heartsmentioning
confidence: 99%
“…Therefore, ectothermic animals can be used to understand mechanisms controlling the electrical and contractile functions of the myocardium in response to changes in environmental temperature. (5)(6)(7) At present there are only a few studies of the electrophysiological processes that occur in a frog's heart ventricle under changes in ambient temperature. (8,9) It has been shown that when the body temperature in the frogs is decreased to 10ºС, then HR is diminished and the durations of QRS and ST-T complexes of ECG are lengthened.…”
Section: Introductionmentioning
confidence: 99%